2021
DOI: 10.48550/arxiv.2102.12461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MAPFAST: A Deep Algorithm Selector for Multi Agent Path Finding using Shortest Path Embeddings

Jingyao Ren,
Vikraman Sathiyanarayanan,
Eric Ewing
et al.

Abstract: Solving the Multi-Agent Path Finding (MAPF) problem optimally is known to be NP-Hard for both make-span and total arrival time minimization. While many algorithms have been developed to solve MAPF problems, there is no dominating optimal MAPF algorithm that works well in all types of problems and no standard guidelines for when to use which algorithm. In this work, we develop the deep convolutional network MAPFAST (Multi-Agent Path Finding Algorithm SelecTor), which takes a MAPF problem instance and attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although solving MAPF optimally is proven to be NP-Hard (Yu and LaValle 2013), many real-world MAPF instances can be solved optimally within a reasonable time. While optimal MAPF algorithms can solve some instances with hundreds of agents, they can also struggle on instances with only a small number of agents (Ren et al 2021;Ewing et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although solving MAPF optimally is proven to be NP-Hard (Yu and LaValle 2013), many real-world MAPF instances can be solved optimally within a reasonable time. While optimal MAPF algorithms can solve some instances with hundreds of agents, they can also struggle on instances with only a small number of agents (Ren et al 2021;Ewing et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The most straightforward small λ 2 example is a map with many narrow corridors. Previous research has shown that various optimal MAPF algorithms have difficulty with such maps even with a small number of agents (Li et al 2020;Ren et al 2021), which could be caused by the over-congestion and conflicts that narrow corridors bring.…”
Section: Introductionmentioning
confidence: 99%